Hoe de Nederlandse juffers met liefde omgingen: De wereld van de gevoelens in Historie van mejuffrouw Sara Burgerhart (1782) van Elisabeth Wolff en Agatha Deken - Urbaniak, Jan (Acta Neerlandica, 2023)
Love played an important role in Wolff and Deken’s 18th-century bestseller, The Historyof Miss Sara Burgerhart. The attitude to the feelings allowed the reader to get to know thenovel’s characters thoroughly. That how they talked about love and made love helped inthe reconstruction of their character drawing. Sara – the title character of the novel – wentthrough a development that also changed her conception of love: from the irresponsibleteenager who enjoyed the company of various, sometimes rowdy boys, she graduallybecame an ideal wife and mother, with whom the sincere love prevailed. In thiscontribution, several models of love in the Sara Burgerhart epistolary novel werecontrasted: the French-tinted, sentimentally colored libertine love game with the calm,reasoned feelings in the Dutch way. The result of such contradiction is easy to guess.